WABAH COVID-19 DALAM PERSPEKTIF TEOLOGI TAKDIR DALAM AJARAN ISLAM - Ali Musri Semjan Putra (Al-Majaalis : Jurnal Dirasat Islamiyah, 2021)
Since WHO declared the corona virus as a pandemic outbreak, various studies have been carried out by authorities and experts in the world from various scientific fields, ranging from the fields of health and medical sciences, education, economics, socio-politics,to the field of religious sciences. In the LIPI study data, there are around 285 research papers discussing the corona virus from various scientific fields’ points of view. In addition, in the study data of Arabic-based papers in Algeria, there are about 131 papers. This does not include the various papers widely spread in scientific journals published by other countries in different languages. However, the topic that becomes the theme of this research is very different from those previous studies. This research will examine the Covid-19 from the perspective of the Theology of Destiny in Islamic teachings. This research will be conducted in the form of a literature review through classical and contemporary Islamic literature with an induction approach using qualitative analysis. humans in making every effort to be free from the Covid-19 pandemic.The conclusion of this research is that the Theology of Destiny destroys atheism, proves human weakness before God's power. Besides, the Theology of Destiny can provide a sense of optimism and motivation for humans in making every effort to survive the Covid-19 pandemic.